Evaluation of CD4+ tumor-infiltrating lymphocyte association with some clinicopathological indices of oral squamous cell carcinoma - Farnaz Mohajertehran; Alieh Farshbaf; Atieh Kashafi; Mehdi Shahabinejad; Shahrzad Ebrahimzade; Abdollah Javan-Rashid; Nooshin Mohtasham (Wolters Kluwer Medknow Publications, 2022)
Background: The delayed diagnosis of oral squamous cell carcinoma (OSCC) affects therapeutic and prognostic strategies, and provides regional recurrence or distant metastasis. The tumor-infiltrating lymphocytes (TILs) are known as a critical diagnostic biomarker in antitumor immune response. We evaluated the association between CD4+ T-lymphocyte marker, some clinicopathological indices, and the impact of TILs on the stage and grade of OSCC. Materials and Methods: In this cross-sectional study, 37 OSCC specimens including 16 early and 21 advanced stages (categorized base-on recent clinical oncology references) and their related healthy surgical margin (as internal control group) were collected. Obtained histochemical data were analyzed by SPSS V.23 software. The expression of CD4+ marker in tumor microenvironment (TME) was compared by nonparametric Mann-Whitney and Kruskal-Wallis as well as Fisher's exact tests. P < 0.05 was remarked statistically significant. Results: The low-grade patients represented more CD4+ TIL that was statistically significant (P = 0.011). However, there was no statistically significant difference in CD4+ TIL between various stages (P = 0.404), tumor size, and lymph node involvement (P > 0.05). Moreover, there was no significant relation between TIL infiltration, age, and tumor localization (P > 0.05), however CD4+ expression in women was more than men (P = 0.008). The CD4+ T-lymphocyte infiltration in TME was more significant than healthy surgical margin (P < 0.001). There was a statistically significant difference between healthy surgical margin and different grades and stages of OSCCs that lower grades demonstrated more CD4+ TIL infiltration (P < 0.001). Conclusion: The CD4+ T-lymphocytes may play important role in differentiation and maturity of epithelial cell, tumorigenesis, and progression of OSCC.